2014
DOI: 10.3758/s13415-014-0321-8
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive activation of newly instructed stimulus–response rules: evidence from lateralized readiness potentials in no-go trials

Abstract: Previous behavioral and electrophysiological evidence has suggested that the instructions for a new choice task are processed even when they are not currently required, indicating intention-based reflexivity. Yet these demonstrations were found in experiments in which participants were set to execute a response (go). In the present experiment, we asked whether intention-based reflexivity would also be observed under unfavorable conditions in which participants were set not to respond (no-go). In each miniblock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
0
45
1
Order By: Relevance
“…We have consistently found that NEXT (screen advancement) responses are slowed in incompatible conditions: the presented stimulus (e.g., “T”) is associated with the opposite response (left) than that used for NEXT responses (Meiran et al, 2015b). Importantly, this “NEXT compatibility effect” is most robust in the first NEXT response, thus meeting the pre requisites we laid out: It represents reflexive behavior since participants are told not to apply the newly instructed rule during the NEXT phase, and it is not due to prior practice 3 .…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 78%
See 3 more Smart Citations
“…We have consistently found that NEXT (screen advancement) responses are slowed in incompatible conditions: the presented stimulus (e.g., “T”) is associated with the opposite response (left) than that used for NEXT responses (Meiran et al, 2015b). Importantly, this “NEXT compatibility effect” is most robust in the first NEXT response, thus meeting the pre requisites we laid out: It represents reflexive behavior since participants are told not to apply the newly instructed rule during the NEXT phase, and it is not due to prior practice 3 .…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 78%
“…Intention-based reflexivity has been found in at least five different behavioral paradigms (Cohen-Kdoshay and Meiran, 2007; De Houwer et al, 2005; Liefooghe et al, 2012; Meiran et al, 2015b; Wenke et al, 2007). Intention-based reflexivity has also been demonstrated at the level of the retrieval of the action plan itself, as seen in the brain lateralized readiness potential (Everaert et al, 2014; Meiran et al, 2014).…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Instruction implementation also has a profound impact on brain activity, as shown by electroencephalography and fMRI studies. In particular, the intention to execute an instruction induces automatic motor activation 8,9 , engages different brain regions to coordinate novel stimuli and responses 1014 , and alters the neural code of the encoded instruction 15,16 .…”
Section: Introductionmentioning
confidence: 99%